Making A Spectacle Of Society: Thoughts on Surreality. (1st March 2018) - Coates, Nigel
Abstract : London‐based architect and designerNigel Coates has had a long and distinguished international career. Here he explores his own work through the lenses of Surrealism, citing some of the influences that shaped his practice and introducing us to his recent project that reimagines London's historic Vauxhall Pleasure Gardens for the 21st century.